Pengaruh Keandalan Akrual Terhadap Persistensi Laba dan Harga Saham: Studi Empiris pada Perusahaan yang Terdaftar di BEI Tahun 2010-2014 - Poppy Melani Qoriza; Mayar Afriyenti (Universitas Negeri Padang, 2016)
This study examine the effect of accrual reliability to earning persistence and stock price, draws on research by Richardson et al. (2005) and Lovelinez and Siti (2012). The population in this study is manufactury company listed on the Indonesia Stock Exchange (IDX) period of 2010-2014. The sample in this study is determined by purposive sampling with 71 companies. Predicted that less reliability of the accrual component, lead to lower the earnings persistence. Lower earnings persistence can not be anticipated by investors leading to security mispricing. The results confirm the prediction that some components of accruals, such as changes in operating assets and current financial liability have different earnings persistence based on the level of reliability. Changes in short-term investments are not anticipated by investors, resulting in a negative stock returns which reflects the low reliability of the accrual components on earnings.Keywords : sccrual reliability, earnings persistence, stock price